1997
DOI: 10.1006/dbio.1996.8466
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transcriptional Activity during the First and Second Cell Cycles in the Preimplantation Mouse Embryo

Abstract: Transcription of endogenous genes in preimplantation 1- and 2-cell mouse embryos was determined by monitoring the incorporation of BrUTP by plasma membrane-permeabilized embryos. Incorporation is observed starting by mid-S phase in the 1-cell embryo and increases progressively; the amount of incorporation by the 1-cell embryo in G2 is about 20% that of the 2-cell embryo in G2. Incorporation by the male pronucleus is always about four to five times greater than that of the female pronucleus. Nevertheless, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
477
1
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 561 publications
(505 citation statements)
references
References 0 publications
21
477
1
6
Order By: Relevance
“…We also validated the BrUTP antibody specificity by substituting BrUTP with UTP ( Figure 4A). Consistent with previous reports [27,28], global transcriptional activity of the paternal genome, which is marked by lack of H3K9me2 staining, is significantly higher than that of the maternal genome ( Figure 4A). …”
Section: Tet3-mediated 5mc Oxidation Is Dispensable For Zygotic Gene supporting
confidence: 93%
See 2 more Smart Citations
“…We also validated the BrUTP antibody specificity by substituting BrUTP with UTP ( Figure 4A). Consistent with previous reports [27,28], global transcriptional activity of the paternal genome, which is marked by lack of H3K9me2 staining, is significantly higher than that of the maternal genome ( Figure 4A). …”
Section: Tet3-mediated 5mc Oxidation Is Dispensable For Zygotic Gene supporting
confidence: 93%
“…RT-qPCR analysis confirmed that the expression dynamics of major satellite DNA and Tet3 previously shown to be unregulated at the 1-cell stage are consistent with previous results [10,29]. This result indicates that some TEs are activated in the 1-cell embryos when global transcription is also initiated [27,28]. The asymmetric nature of 5mC oxidation in zygotes prompted us to ask whether activation of the TEs in zygotes exhibits allele specificity.…”
Section: Te Expression From Both Paternal and Maternal Alleles In 1-csupporting
confidence: 87%
See 1 more Smart Citation
“…40 HDACs likely underlie development of the transcriptionally repressive state because inducing histone hyperacetylation using HDAC inhibitors not only relieves the enhancer requirement for efficient expression of plasmid-borne reporter genes in 2-cell embryos, 83,84 but also results in a further increase in global transcription. 85 Several lines of evidence support a role for HDAC1 in development of a transcriptionally repressive state that initiates in 2-cell embryos. 42 First, microarray data and qRT-PCR show that Hdac1 is zygotically expressed beginning from 2-cell stage, 42,86,87 accompanying genome activation.…”
Section: Hdac1 Is the Responsible Hdac Involved In Cell Cyclementioning
confidence: 99%
“…Firstly, PRC1.6 is the only PRC1 complex that, in addition to catalytic activity toward H2AK119, possesses histone deacetylation activity 13 and, therefore, could also contribute to the rapid changes in histone acetylation that characterize pre-implantation development. 1,2,4 Secondly, PRC1.6 contains a recognition module, through L3MBTL2, for H4K20me1, which is essential for pre-implantation development, as deletion of PR-Set7 results in lethality by the 8-cell stage, in a manner dependent of its methyltransferase activity. 13,21 Since L3MBTL2 is a defining, unique feature of PRC1.6, we therefore assessed its localization through preimplantation development.…”
Section: L3mbtl2 a Specific Subunit Of Non-canonical Prc16 Complex mentioning
confidence: 99%